2023
DOI: 10.3390/sym15051027
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Urdu Sentiment Analysis Using Machine and Deep Learning Techniques for Two-Class Classification of Symmetric Datasets

Abstract: Many investigations have performed sentiment analysis to gauge public opinions in various languages, including English, French, Chinese, and others. The most spoken language in South Asia is Urdu. However, less work has been carried out on Urdu, as Roman Urdu is also used in social media (Urdu written in English alphabets); therefore, it is easy to use it in English language processing software. Lots of data in Urdu, as well as in Roman Urdu, are posted on social media sites such as Instagram, Twitter, Faceboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Mahmood et al [28] presented a deep learning model to extract emotions and attitudes of people expressed in R-Urdu, where RCNN outperformed baseline approaches with accuracy scores of 0.652% and 0.572% for binary and ternary classifications, respectively. K. B. Muhammad and S. M. Aqil Burney [50] applied machine and deep learning algorithms for Urdu text Classification of symmetric datasets. They found that machine learning algorithms showed good results, while most deep learning algorithms improved the results further.…”
Section: Deep Learning Based Sentiment Analysis Of Urdu Textmentioning
confidence: 99%
“…Mahmood et al [28] presented a deep learning model to extract emotions and attitudes of people expressed in R-Urdu, where RCNN outperformed baseline approaches with accuracy scores of 0.652% and 0.572% for binary and ternary classifications, respectively. K. B. Muhammad and S. M. Aqil Burney [50] applied machine and deep learning algorithms for Urdu text Classification of symmetric datasets. They found that machine learning algorithms showed good results, while most deep learning algorithms improved the results further.…”
Section: Deep Learning Based Sentiment Analysis Of Urdu Textmentioning
confidence: 99%
“…Yadav andVishwakarma 2020, Saberi andSaad 2017), is now becoming popular in other low resource languages like Urdu (e.g. Noor et al 2019, Muhammad andBurney 2023), Pashto (e.g. Iqbal et al 2022, Kamal et al, Kamal et al), Bangla (e.g.…”
Section: Related Workmentioning
confidence: 99%